Geestelijke verzorging in een levensbeschouwelijk divers en geseculariseerd land - Berghuijs, Joantine (Religie & Samenleving, 2020)
Measured in terms of church membership and church attendance, The Netherlands are rapidly secularizing. However, the country has a very diverse population in terms of religious/spiritual orientations, including the phenomenon of ‘multiple religious belonging’ that cuts through all traditional divisions. All in all, there is a majority of over 60% that is involved in some form of religion or spirituality. In most cases, interfaith spiritual care is unproblematic for both spiritual caregivers and for their clients, except in case of religion-specific rituals. Recent developments enhance the presence and visibility of spiritual caregivers and their broad employability. Concerns about profiling of the profession, and fragmentation of types of accreditation are discussed.